Characterisation of prostate cancer using texture analysis for diagnostic and prognostic monitoring. (27th February 2021) - Singh, Dharmesh; Kumar, Virendra; Das, Chandan J.; Singh, Anup; Mehndiratta, Amit
Abstract : Automated classification of significant prostate cancer (PCa) using MRI plays a potential role in assisting in clinical decision‐making. Multiparametric MRI using a machine‐aided approach is a better step to improve the overall accuracy of diagnosis of PCa. The objective of this study was to develop and validate a framework for differentiating Prostate Imaging‐Reporting and Data System version 2 (PI‐RADS v2) grades (grade 2 to grade 5) of PCa using texture features and machine learning (ML) methods with diffusion‐weighted imaging (DWI) and apparent diffusion coefficient (ADC). The study cohort included an MRI dataset of 59 patients with clinically proven PCa. Regions of interest (ROIs) for a total of 435 lesions were delineated from the segmented peripheral zones of DWI and ADC. Six texture methods comprising 98 texture features in total (49 each of DWI and ADC) were extracted from lesion ROIs. Random forest (RF) and correlation‐based feature selection methods were applied on feature vectors to select the best features for classification. Two ML classifiers, support vector machine (SVM) and K‐nearest neighbour, were used and validated by 10‐fold cross‐validation. The proposed framework achieved high diagnostic performance with a sensitivity of 85.25% ± 3.84%, specificity of 95.71% ± 1.96%, accuracy of 84.90% ± 3.37% and area under the receiver‐operating characteristic curve of 0.98 for PI‐RADS v2 grades (2 to 5) classification using the RF feature selection method and Gaussian SVM classifier with combined features of DWI + ADC. The proposed computer‐assisted framework can distinguish between PCa lesions with different aggressiveness based on PI‐RADS v2 standards using texture analysis to improve the efficiency of PCa diagnostic performance. Abstract : This study investigated the role of machine learning‐based texture analysis approaches for classification of prostate cancer grades based on PI‐RADS v2. Of all the texture features, GLRLM‐, LTEM‐ and Gabor‐wavelet–based features were mainly found to be good markers for classification. The proposed framework displayed high performance (accuracy = 93.80% for LG vs. IG vs. HG and accuracy = 91% for grade 4 vs. grade 5 classifications) using the random forest feature selection method and Gaussian SVM classifier with combined texture features of DWI + ADC.